Pleural empyema caused by dropped gallstones after laparoscopic cholecystectomy for acute cholecystitis: a case report - Aya Tokuda; Hiromitsu Maehira; Hiroya Iida; Haruki Mori; Nobuhito Nitta; Takeru Maekawa; Katsushi Takebayashi; Sachiko Kaida; Toru Miyake; Ryo Kuroda; Haruka Yamamoto; Masaji Tani (Surgical Case Reports)
Abstract Background Dropped gallstones during laparoscopic cholecystectomy (LC) sometimes induce postoperative infectious complications. However, pleural empyema rarely occurs as a complication of LC. Case presentation We present the case of a 66-year-old woman with right pleural empyema. She previously underwent LC for acute gangrenous cholecystitis 11 months ago. The operative report revealed iatrogenic gallbladder perforation and stone spillage. The bacterial culture of the gallbladder bile was positive for Escherichia coli. Chest and abdominal computed tomography revealed right pleural effusion, perihepatic fluid collection, and multiple small radiopaque density masses. Although ultrasound-guided transthoracic drainage was performed, the drainage was incomplete, and systemic inflammatory reaction persisted. Consequently, thoracotomy and laparotomy with gallstone retrieval were performed, and the patient recovered completely. The patient has remained well without complications after 14 months of follow-up. Conclusions We report a rare case of pleural empyema caused by dropped gallstones after LC. This case emphasized the importance of completely retrieving the dropped gallstones to prevent late infectious complications after LC.